Dynamic Effects of Licensing and Knowledge Transfer across Research Stages: Evidence from the Pharmaceutical Industry - Zhili Tian; Ralph Siebert (Center for Economic Studies and Ifo Institute (CESifo), 2020)
In the pharmaceutical industry, firms frequently engage in licensing agreements to overcome innovation challenges and keep up with the pace of developing new drugs. Licensing helps firms jointly develop new drugs and acquire external knowledge, which helps improve their internal drug development capability. Our study examines the dynamic effects of licensing on the success of the licensees' internal drug development across research stages. We adopt a structural equation modeling approach and find that external knowledge transfer via licensing can have differential effects on firms' internal research stage-specific R&D capabilities. The success of transferring external knowledge to an in-licensing firm is critically dependent on the firm's internal R&D capabilities, their financial capability, and the research stage. We find that license agreements formed at the early stage (the discovery and preclinical test phases) and intermediate stage (phase 1 and 2 clinical test phases) exert strong direct and short-run effects on internal R&D capabilities in the same research stages. Moreover, licensing formed at the intermediate stage exerts remarkably strong indirect and long-run effects that impact R&D capabilities in successive research stages. Licensing in the late stage (phase 3 clinical test and product approval) is costly and does little to enhance firms' internal R&D capabilities. Our results also show that licensing is formed among firms with stronger financial resources, and those resources are necessary for a successful technology transfer. Our results also provide insights into the impact of licensing on project success rates across research stages.
Keywords: L24; L25; L65; D22; 330; pharmaceutical drug development; licensing; R&D capabilities; effects of licensing on R&D capabilities